Pendampingan Pembuatan Masterplan Desa Wisata Mekarsari Narmada - Ummu Latifa; Febria Handayani; Safira Indana Masrura; Suci Sukma; Yazman Yazid; Munawir Ali Sahbana; Siska Dewi Wulandari; Sabina Permata Ridyati; Muhammad Mujahid Dakwah (Pusat Riset dan Inovasi Nasional, 2024)
Assistance in making a masterplan is carried out by MBKM Building Villages students located in Mekarsari Village which aims to assist the village government in developing and exploring the potential of Mekarsari Village as a tourist village. By becoming a tourist village, the village is expected to be able to become an independent village that can independently manage its economy. The method of preparing the masterplan was conducted by focus group discussion (FDG), discussing the problems and potentials of the village. It is expected that the final result of this masterplan preparation assistance can provide great benefits and contributions to the development and development of the village.